Continuous wave pumped single-mode nanolasers in inorganic perovskites with robust stability and high quantum yield. Issue 28 (5th July 2018) - Jiang, Li; Liu, Renming; Su, Rongling; Yu, Ying; Xu, Haofei; Wei, Yuming; Zhou, Zhang-Kai; Wang, Xuehua
Abstract : A one-step and surfactant-free method is proposed to synthesize inorganic perovskite (CsPbX3, X = Cl, Br, I) nanowires at room temperature. The as-prepared CsPbX3 nanowires exhibit high lasing quantum yield, single-mode lasing with ultra-narrow linewidth. Abstract : Perovskite lasers have aroused great interest in recent years due to their ultra-low lasing threshold, high quantum yields, easily tuned emission colors and great potential for electrically pumped nanolasing, which opens up new possibilities in obtaining highly coherent light sources at the nanoscale. Compared with the widely studied organic–inorganic hybrid perovskites, the inorganic (CsPbX3 ) have gradually become an emerging research focus because of their relatively better stability. However, some problems still hinder their actual applications, such as the seldom explored lasing quantum yield and the difficulties of further improving stability. Herein, a simple method is proposed to synthesize CsPbX3 nanowires in ambient conditions, and these CsPbX3 nanowires exhibit perfect crystallization and outstanding stability (over 1 year). Perovskite lasing with single mode and a low threshold of 12.33 μJ cm −2 as well as a high lasing quantum yield up to ∼58% are obtained. More interestingly, a high quality single-mode laser with ultra-narrow linewidth of 0.09 nm can be obtained when the CsPbX3 NWs are excited by continuous wave in low-temperature condition. Our results not only enrich the study of inorganic perovskite materials with a new synthetic method, but also uncover new lasing properties of CsPbX3 NWs, suggesting a broad application of the inorganic perovskite materials.